The Effect of Environmental Sanitation on the Incidence of Stunting in the Working Area of the Tanjung Pinang Community Health Center, Jambi City - Subakir, Subakir; Listiawaty, Renny; Suroso, Suroso (Program Studi Ilmu Kesehatan Masyarakat, Universitas Jambi, 2025)
Stunting in toddlers remains a public health problem in Indonesia, including in Jambi City. Environmental sanitation factors, family hygiene practices, and parental access to health information are suspected to contribute to stunting. This study aims to analyze the relationship between drinking water quality, clean water facilities, family latrines, water storage, exposure to digital parenting, and family hygiene practices with stunting in toddlers in the Tanjung Pinang Community Health Center (Puskesmas) working area of Jambi City. The study design was a case-control study with a total sample of 140 respondents, consisting of 35 cases (toddlers with stunting) and 105 controls (toddlers without stunting). Data were collected through structured questionnaires, observations, and anthropometric measurements. The analysis was conducted using the Chi-square test and followed by adjusted multiple logistic regression to control for confounding variables. The results showed that several variables had a significant relationship with stunting incidence. After being included in the adjusted multivariate model, physical water quality was recorded as the most dominant factor influencing stunting incidence in the study area. This finding confirms that efforts to reduce stunting require not only improving sanitation infrastructure but also strengthening behavior-based health education and the use of digital media for parents. Multisectoral interventions that combine physical sanitation improvements with strengthening digital health literacy are recommended to support accelerated reduction in stunting prevalence.